Typologies and precursors of career adaptability patterns among emerging adults: A seven‐year longitudinal study. Issue 8 (27th June 2014) - Shulman, Shmuel; Vasalampi, Kati; Barr, Tamuz; Livne, Yaara; Nurmi, Jari‐Erik; Pratt, Michael W.
ABSTRACT: The present study examined career adaptability in 100 Israeli emerging adults who were followed from ages 22 to 29. Participants were given an in depth interview and were asked to talk about their current work, difficulties they might have had in the past and how they coped with them. In addition they were asked to elaborate on the extent to which their job fits their interests and is meaningful to them. Analyses of interviews yielded three distinctive career adaptability patterns that were associated with different levels of concurrent wellbeing: Integrated, Compromised, and Vague. A lower level of identified motivation measured seven years earlier predicted membership in the Compromised pattern. A higher level of extrinsic motivation combined with decreased parental support predicted membership in the Vague pattern. Findings are discussed within the framework of the occupational adaptations and compromises that young people must make when approaching the age of 30.